The combination of neutrophil to lymphocyte ratio and platelet to lymphocyte ratio improves accuracy of neonatal sepsis diagnosis - Rocky Wilar; Beatrice Koesmarsono; Stefanus Gunawan (Indonesian Pediatric Society, 2023)
Background Neonatal sepsis remains a challenging issue, due to sophisticated and time consuming tests needed to confirm a diagnosis. Objective To assess the applicability of neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) as diagnostic markers in neonatal sepsis. Methods This cross-sectional study was conducted in the Neonatology Ward of Kandou General Hospital, Manado, North Sulawesi. Neonates with suspected sepsis were included by consecutive sampling. We measured NLR and PLR form hematology profiles and differential count. Diagnosis of neonatal sepsis was based on positive blood cultures. A receiver operating characteristic (ROC) curve analysis was done to assess the NLR and PLR cut-off points. Chi-square test was used to analyze the diagnostic value of NLR and PLR. Results A total of 176 full term neonates with suspected sepsis were included in the study. Of these, 84 (47.7%) subjects were confirmed with neonatal sepsis and 92 (52.3%) were non-sepsis. The mean NLRs were 5.9 (95%CI 2.0 to 13.6) in the sepsis group and 1.6 (95%CI 0.2 to 3.2) in the non-sepsis group. A NLR of 3.0 was determined as the predictive cut-off value of neonatal sepsis (sensitivity 94%, speci?city 97.8%, and area under the ROC curve 0.995). NLR can effects on neonatal sepsis diagnosis by 61% . The mean PLRs were 79.9 (95%CI 44.0 to 155.8) in the sepsis group and 44.0 (95%CI 9.7 to 91.8) in the non-sepsis group. A PLR of 60.4 was determined as the predictive cut-off value of neonatal sepsis (sensitivity 86.9%, speci?city 87%, area under ROC curve 0.928). PLR can effects on neonatal sepsis diagnosis by 47.5%. When NLR and PLR were combined, they can improve accuracy of neonatal sepsis diagnosis about 72.2%. Conclusion Neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) can be used in combination as adjunct diagnostic tests for neonatal sepsis workups.